Proteomic and metabolomic insights into the impact of topping treatment on cigar tobacco - Guo, Dong; Gao, Huajun; Yan, Tongjing; Xia, Changjian; Lin, Beisen; Xiang, Xiaohua; Cai, Bin; Geng, Zhaoliang (Frontiers in Plant Science, 2025)
Top removal is a widely utilized method in production process of tobacco, but little is known regarding the way it impacts protein and metabolic regulation. In this study, we investigated the underlying processes of alterations in cigar tobacco leaves with and without top removal, using a combined proteomic and metabolomic approach. The results revealed that: (1) Topping significantly affected superoxide anion (O2 -) levels, superoxide dismutase (SOD) activity, and malondialdehyde (MDA) content, (2) In the cigar tobacco proteome, 385 differentially expressed proteins (DEPs) were identified, with 228 proteins upregulated and 156 downregulated. Key pathways enriched included flavonoid biosynthesis, porphyrin and chlorophyll metabolism, cysteine and methionine metabolism, and amino acid biosynthesis and metabolism. A network of 161 nodes interconnected by 102 significantly altered proteins was established, (3) In the cigar tobacco metabolome, 247 significantly different metabolites (DEMs) were identified, with 120 upregulated and 128 downregulated metabolites, mainly comprising lipids and lipid-like molecules, phenylpropanoids and polyketides, organic acids and derivatives, and organic heterocyclic compounds, (4) KEGG pathway enrichment revealed upregulation of proteins such as chalcone synthase (CHS), chalcone isomerase (CHI), naringenin 3-dioxygenase (F3H), and flavonoid 3'-monooxygenase (F3'H), along with metabolites like pinocembrin, kaempferol, trifolin, rutin, and quercetin, enhancing the pathways of 'flavonoid' and 'flavone and flavonol' biosynthesis. This study sheds light on the metabolic and proteomic responses of cigar tobacco after topping.